Youth Identity at the Crossroad of Originality and Modernity - Smail Benalia (Social Empowerment Journal, 2023)
There is a wide consensus in the academic debate that youth and social identities have always been associated with the controversy between originality and modernity. The latter erupted an identity crisis whose dimensions are evident in society in general and among youth in particular. Indeed, the issue of identity has been placed on the top of social agenda especially in light of challenges that are gradually removing the societal privacy barriers, denying the national entity, and destroying the foundations of sectarian and ethnic classification. Undoubtedly, technology has played a central role in the breach of identity as it systematically promotes a cultural dependency which contradicts our deep-rooted values ​​and thus erases our authentic cultural existence. Since young people are the most responsive group to societal change, their central identity and their cultural dimensions of belonging are at stake. Henceforth, this research paper provides a sociological approach to the issue of identity; among young people, which fluctuates between commitment and disintegration, awareness and dispersion, and between originality and change in light of the social rift associated with dynamic and technological changes.